Adopting Planned Behavior Theory to Investigate the Effect of Entrepreneurship Education on Students' Entrepreneurial Intention - Reni Dwi Astuti; Laelati Fatimah (STAI Hubbulwathan Duri, 2022)
To support the Government's program to produce entrepreneurs, FTI UAD implements entrepreneurship education. The purpose of the study was to determine the effect of entrepreneurial knowledge obtained from entrepreneurship education, either directly or through the Theory of Planned Behavior (TPB) component, in the form of attitudes and perceived behavioural control. The study was also to determine the effectiveness of TPB in describing the entrepreneurial intentions of FTI UAD students. The sample used was 205 undergraduate students who had taken entrepreneurship courses. Data was collected using a questionnaire. Data analysis used linear regression and path analysis. The results showed an indirect effect of entrepreneurial knowledge on entrepreneurial intentions through attitudes and perceived behavioural control. However, knowledge does not have a direct impact on entrepreneurial intentions. The study results prove that the TPB model to describe entrepreneurial intentions is quite good, with the magnitude of the coefficient of determination reaching 58.1%.